Analysing the efficiency of local and foreign cars in Malaysia using Data Envelopment Analysis (DEA) / Khairul Sanusi Samuil and Anas Fathul Ariffin - Samuil, Khairul Sanusi; Ariffin, Anas Fathul (College of Computing, Informatics and Media, UiTM Perlis, 2023)
The most important aspect in choosing your car is quality and durability and most people tend to ignore them as the car visualisation and well-known car seems to be the more important point. On the other hand, different size of wages for each individual shows that there is a specific car that matched their ability to pay and still have an impressive balanced in their bank account. This research helps people to value all the car that suits them by using Data Envelopment Analysis (DEA). DEA is a non-parametric approach used to analyse the relative efficiency of decision-making units (DMUs) under conditions where multiple inputs and multiple outputs are present. All the data on cars’ specifications have been collected and converted to DEA-Solver, a software that measured the car’s efficiency and effectiveness. ZIGWHEELS website is the platform for choosing all those cars and 25 cars had been chosen according to their best car in each segment (sedan, hatchback, MPV, and SUV) between 2020- 2021 along with the specifications found on WAPCAR websites. The inputs and outputs chosen are top speed, horsepower, torque, safety recognition, price, service cost, fuel consumption, and engine capacity. As the result, few cars do not reach the efficiency value of 1 or inefficient DMUs, therefore, helping people to choose cars of their own and can save some time in choosing which car is the best for them.